The goals and governance of the social inclusion and community activation programme (SICAP) 2015-2017: a mixed methods study - Darmody, Merike; Smyth, Emer (ESRI)
The study, part of an on-going research programme, found that the most vulnerable participants on the Social Inclusion and Community Activation Programme (SICAP) 2015-2017, funded by the Department of Rural and Community Development and administered by
PUBLISHED